Public participation in a West of England energy transition: Key patterns and trends - Barnes, J (University of Oxford, 2019)
This report addresses the question: how and where is public participation in energy systems occurring in the West of England? To achieve deep and timely cuts to carbon emissions, fundamental changes to the way society produces and consumes energy is required. That unfolding energy transitions will require changes in technologies and infrastructures is largely taken for granted. That they will also require the active engagement and participation of citizens is slowly becoming more widely accepted, for three connected reasons: to achieve a transition will require (1) fundamental changes to individual and collective energy practices, (2) acceptance of the direction and extend of change, as well as (3) a willingness to pay for it. As a result, the involvement of citizens and the fostering of public participation has subsequently emerged as a central concern for those interested in building increasingly sustainable and inclusive energy systems. Traditionally, citizens have been viewed as passive energy consumers and public participation in energy system developments have typically amounted to periodic consultations on singular issues. Today, the ways in which citizens are participating in energy systems is thought to be much more diverse. The rise of community renewables projects presents one example. Citizen science initiatives another. Visioning exercises, participatory planning processes, hacker spaces, smart technology trials and ‘city labs’ are all further examples of the diverse ways in which citizens are actively shaping energy system developments and contributing to collective decisions about their energy futures. In response attention has sought to explore the diversity of contemporary energy participation in the UK (Pallet et al., 2017). Less understood and, to date, little studied, is the extent and diversity of public participation occurring in particular places, such as the West of England. This report, the outcome of a project funded by the Bristol Sustainable Energy Research Fund1 , seeks to address this gap by answering the q